The use of argon plasma coagulation in mammoplasty as a prevention of postoperative complications - A. V. Kozlov; P. A. Fedorova; A. S. Anashkina; D. A. Kim; T. N. Kozlova (Сибирский научный медицинский журнал, 2022)
The frequency of reoperations associated with complications after mammoplasty reaches 15 % during the first year. There are many ways and means for processing the soft tissues of the breast during mammoplasty, helping to reduce the risk of postoperative complications. The purpose of this work was to develop an algorithm for the application of the argon plasma technique for tissue treatment in mammoplasty. Material and methods. The study included 30 females aged 23 to 46 who underwent mammoplasty. The patients were divided into 2 groups of 15 people. In group 1, standard methods of processing soft tissues were used, and in group 2, the argon plasma technique was used in conjunction with the use of Aristo glue. Patients were observed in the early, late and distant postoperative period. Results. In the course of the study, in addition to the excellent coagulation and bactericidal action of argon plasma, the effect of “pulling up” the soft tissues of the mammary gland was found, which, in case of ptosis of I and II degrees, made it possible to use a smaller implant to achieve an optimal aesthetic result. Also, when using the argon plasma technology, no inflammatory processes were observed, the amount of exudative fluid in the drains decreased, the pain syndrome was significantly less pronounced in comparison with patients who underwent the standard method of tissue processing. Conclusions. This study confirms the fact that the use of argon plasma coagulation in the processing of breast tissue has a significant number of advantages compared to standard methods.